Application of Internet of Things Technology for Ventilation and Environmental Control in Conventional Open-Air Pig Housing Systems in Thailand - Suphalerk Khaowdang; Nopparat Suriyachai; Saksit Imman; Kowit Suwannahong; Surachai Wongcharee; Torpong Kreetachat (AgriEngineering)
This study examined the effectiveness of using Internet of Things (IoT) technology to control environmental conditions in open-air pig housing systems in Thailand. This experiment was conducted in three zones: Zone 1, with no environmental controls (natural ventilation); Zone 2, with ventilation fans but no water-spraying system; and Zone 3, equipped with both ventilation fans and a roof-mounted water-spraying system. Key parameters, such as ammonia (NH3), hydrogen sulfide (H2S), temperature, and relative humidity, were monitored all year round. Zone 1, with only natural ventilation, exhibited the highest levels of pollutants, with an average ammonia concentration of 7.1 ppm and hydrogen sulfide at 7.6 ppm. The temperature averaged 31.81 °C, and the relative humidity was 53.65%, creating unfavorable conditions for pig farming. Zone 2, featuring ventilation fans, showed improvements, with the average ammonia and hydrogen sulfide levels reduced to 3.75 ppm and 4.12 ppm, respectively, although the temperatures (29.35 °C) were still too high at times, and the relative humidity was 49.50%. Zone 3, incorporating both fans and a water-spraying system, demonstrated the most effective environmental control, achieving lower ammonia (3.0 ppm) and hydrogen sulfide (2.93 ppm) levels, with an average temperature of 28.85 °C and relative humidity of 47.15%. These results suggest that IoT technology, combined with adequate ventilation and cooling systems, significantly enhances environmental conditions, thereby promoting better pig health and growth.